The uproar surrounding petroleum contract renegotiations - Kahale, G (Oxford Institute for Energy Studies, 2010)
In recent years, complaints of unfairness on the part of host states in the renegotiation of international petroleum contracts have become commonplace at conferences and seminars in both the United States and Europe. Not so often discussed are the legal issues underlying the particular cases – simply repeating the mantra of pacta sunt servanda is not a discussion. Even less attention is paid to the facts, a point which is the focus of this article. Without an understanding of the facts underlying a renegotiation, one can easily jump to the wrong conclusions, and that is precisely what seems to have been happening with alarming frequency on the conference/ seminar circuit, where conclusions are too often drawn from incomplete information derived from press releases or press reports.